EFFECT OF THE MANTLE OF THE EXPERT IN STUDENTS’ GEOMETRY ACHIEVEMENT (ANGLES AND POLYGONS) - Sahar M M Barghouthi; Hutkemri Zulnaidi; Nofouz Mafarja (MOJES: Malaysian Online Journal of Educational Sciences, 2023)
Issues about poor achievement in mathematics (angles and polygons topics) among Palestinian students has led to the need for developing new effective strategies that can be used to improve mathematics achievement among Palestinian 7th grade students. The aim of study is to reveal the effect of employing the mantle of the expert on the achievement of angles and polygons topics among seventh grade students in Palestine. A quasi-experimental non-equivalent control group design using experimental and control groups with a pre and post-test was conducted. Data were collected using achievement test. The sample of study consisted of (76) students in the seventh grade that were divided into two groups, the experimental group (37) students and the control group (39) students. Data collected from the pre-test and post-test was analyzed using descriptive and inferential statistics. One-way MANOVA test was used to verify the differences of achievement between experimental and control groups. The research found that there is a significant impact of employing the mantle of the expert in increasing the achievement in geometry among seventh grade students. Students who are studied using mantle of the expert had better achievement than those who did not. This study recommended employing the mantle of the expert in teaching other topics in mathematics and in different study stages. This study too showed the necessity of paying attention to the use of classroom and extra-curricular activities in different academic subjects, particularly in mathematics, as well as indicated the necessity of holding courses and workshops to train teachers to use the mantle of the expert in the educational process.